L’edificio D, lo scavo delle deposizioni votive e la dedica a Thufltha (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2019)
This contribution explores the possible reconstructions of the series of actions that led to the formation of the votive deposit found by P. Romanelli inside building D. It analyses the bronze elements found among the bulk of finds dating between the end of the 3rd and the beginning of the 2nd century BCE: a twig and a small inscribed rod dedicated to Thufltha. This association of elements seems to support the identification of Thufltha with Favor, or the Favores Opertanei, which has already been suggested by a number of scholars.
Keywords: Tarquinia; Civita; building d; votive deposit; excavations by P. Romanelli; bronze twig and small rod; Thufltha